2021
DOI: 10.7554/elife.72456
|View full text |Cite
|
Sign up to set email alerts
|

Tightly coupled inhibitory and excitatory functional networks in the developing primary visual cortex

Abstract: Intracortical inhibition plays a critical role in shaping activity patterns in the mature cortex. However, little is known about the structure of inhibition in early development prior to the onset of sensory experience, a time when spontaneous activity exhibits long-range correlations predictive of mature functional networks. Here, using calcium imaging of GABAergic neurons in the ferret visual cortex, we show that spontaneous activity in inhibitory neurons is already highly organized into distributed modular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 53 publications
5
30
0
Order By: Relevance
“…43,44 Recent experimental results have suggested that inhibitory neurons drive decorrelation of neural activities. 45,46 In line with these results, in our model, interconnected inhibitory neurons repel each other and their tuning curves decorrelate (Fig. 2D).…”
supporting
confidence: 86%
“…43,44 Recent experimental results have suggested that inhibitory neurons drive decorrelation of neural activities. 45,46 In line with these results, in our model, interconnected inhibitory neurons repel each other and their tuning curves decorrelate (Fig. 2D).…”
supporting
confidence: 86%
“…At eye opening, excitatory networks display modular patterns of activity for both spontaneous and evoked activity, and initial cellular orientation preferences are already established 4 , 6 , 7 . A recent study suggested that GABA-INs also display modular patterns of spontaneous activity before eye opening 21 . In contrast, we show that modular patterns are not evident for visually-evoked activity and orientation tuning is not well established for GABA-INs at eye opening.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral connectivity of cortical neurons is known [27] to have an ON center OFF surround neighborhood connectivity. But the only hint that the tuned response in vessels gives is that there is a possibility of competitive learning among them, most likely brought about by inhibitory lateral connections [16]. To verify this, we varied the lateral architecture of vessels in the NV-LIN in three possible ways, (i) No lateral connectivity, (ii) ON center OFF surround, and (iii) OFF center ON surround.…”
Section: Discussionmentioning
confidence: 99%
“…In computational neural models, orientation selectivity of neurons often arises from the competitive learning facilitated by the distant lateral inhibitory connections [27]. Latest experimental studies also support the existence of such long range inhibitory connections among cortical neurons facilitating the self-organizing ability of the cortex during the developmental stage [16]. Since the vascular network also exhibits tuned responses, it indicates the possibility of inhibitory lateral connections among the vessels, which enable competitive learning.…”
Section: The Lateral Connectivity Architecture In the Vesselsmentioning
confidence: 99%
See 1 more Smart Citation